Improved Determination of Apparent and Plastic Viscosity for Aqueous Solution of Drilling Fluid Additives - Dilip K. Rajak; Akhilendra K. Pathak; Chandan Guria (International Journal of Petroleum Technology, 2014)
Rheological behavior of drilling fluids is very complex. Exact determination of shear rates helps to predict apparent and plastic viscosity very accurately, which will help to monitor drilling operation efficiently. This paper deals with the improved estimation of shear rates of drilling fluids with varying rotor rotation using coaxial-cylinder Fann viscometer, which is based on generalized difference equation under purely steady, laminar and isothermal tangential fluid flow condition. Rotor rotating speeds and bob dial readings are the input variables for shear rate prediction. The proposed equation was used to calculate shear rates accurately (hence apparent, plastic viscosity and yield point) for several non-Newtonian fluids, mainly, aqueous suspension of bentonite, xanthan gum, poly anionic cellulose and carbomethoxy cellulose solution. Finally, the predicted consistency plots were compared with those which are obtained from the conventional method of estimating the rate of shear for drilling fluids.